“With which one need have no fear of death, or dread dying of any wound”: About the effects of fierabras balm in don Quixote - Sancho Dobles, Leonardo (2015)
From the elaboration and the effects of “Fierabras balm” in the novel of Miguel de Cervantes The Ingenious Gentleman Don Quixote of La Mancha, it explores the “Speech about the arms and the letters” in which the character establishes a distinction between the student and the soldier and this last one is privileged for his constant confrontation with the death. Finally, the magic balm and the subject of the death are taken as a reference in the walking knight and nexus are woven between the publications of the Cervantes text of 1605 and that one of 1615.